Diversity, distribution patterns, and ethnobotanical utilizations of aromatic plant species in Sitakunda Botanical Garden and Eco-park, Bangladesh - Dutta, Shourav; Kamal Hossain, Mohammed (Ethnobotany Research and Applications, 2025)
Background: Sitakunda Botanical Garden and Eco-park is a biodiversity-rich hill forest in the Chattogram district, Bangladesh that harbors a wide range of aromatic plant species. However, the diversity of these species is facing a serious onslaught due to multiple anthropogenic disturbances. This study was carried out to evaluate the current status, diversity, distribution patterns, and ethnobotanical uses of aromatic plant species in this eco-park. Methods: Field data were collected using the random quadrat method across 48 plots at various elevations. Ethnobotanical data were gathered through Focus Group Discussions (FGDs) with local communities and categorized into five use categories based on plant habit. Community structure was assessed using biodiversity indices, including Shannon’s Index, Simpson’s Index, Species Diversity Index, Margalef’s Richness Index, and Species Evenness Index. Results: A total of 1284 individuals representing 27 aromatic plant species from 26 genera and 22 families were documented. The families Asteraceae and Lauraceae were the most represented each with three species, followed by Zingiberaceae with two species. The calculated biodiversity indices were Shannon’s Index (4.07), Simpson’s Index (0.84), Species Diversity Index (3.08), Margalef’s Richness Index (0.97), and Species Evenness Index (2.05). Conclusions: This study revealed that medicinal aromatics performed a significant role in supporting biodiversity, preparing traditional medicines, sustaining religious and cultural heritage. Findings of the study recommended that the sustainable management of these plant resources is urgently needed to counteract the impact of human activities and to preserve the ethnobotanical heritage of the region. Keywords: Aromatic plant; Bangladesh; Conservation; Importance Value Index; Plant diversity; Potential utilizations.